Counterpoetics of modernity : on Irish poetry and modernism - Lloyd, David, 1955 December 20- (Edinburgh : Edinburgh University Press, 2022)
"This study puts contemporary Irish poetry in dialogue with major debates and concerns of European and American poetics. David Lloyd tracks the traits of Irish poetic modernism, from fragmentation to the suspicion of representation, to nineteenth-century responses to the rapid and unsettling effects of Ireland's precocious colonial modernity, such as language loss and political violence. He argues that Irish poetry's inventiveness is driven by the need to find formal means to engage with historical conditions that take from the writer the customary certainties of cultural continuity, identity and aesthetic or personal autonomy, rather than by poetic innovation for its own sake. This reading of Irish poetry understands the innovative impetus that persists through Irish poetry since the nineteenth century as a counterpoetics of modernity. Opening with chapters on Mangan and Yeats, the book then turns to detailed discussions of Trevor Joyce, Maurice Scully, and Catherine Walsh; major Irish contemporary poets never before the focus of a book-length study." -- Provided by publisher
Introduction: Counterpoetics and Colonial Modernity -- Part I: Spectres of Modernity. Overture: The Burden of Discontinuity: Criticism, Colonialism and Anti-Modernism -- Crossing Over: On James Clarence Mangan's "Spirits Everywhere" -- 1913-1916-1919: Yeats's Dates -- 'To Live Surrounded by a White Song', or, The Sublimation of Race in Experiment: On the Margins of Susan Howe -- Part II: New Things That Have Happened. New Things That Have Happened: Forms of Irish Poetry -- Intricate Walking: Scully's Livelihood -- Rome's Wreck: Joyce's Baroque -- Conclusion: Conduits for the Humane: Walsh's Optic Verve.
Includes bibliographical references (pages 202-212) and index.
Keywords: Irish poetry -- 19th century -- History and criticism; Irish poetry -- 20th century -- History and criticism; Irish poetry -- 21st century -- History and criticism; European poetry -- History and criticism; American poetry -- History and criticism; Poésie irlandaise -- 19e siècle -- Histoire et critique; Poésie irlandaise -- 20e siècle -- Histoire et critique; Poésie irlandaise -- 21e siècle -- Histoire et critique; Poésie européenne -- Histoire et critique; Poésie américaine -- Histoire et critique; American poetry; European poetry; Irish poetry; 1800-2099; Criticism, interpretation, etc